Heme regulates protein interactions and phosphorylation of BACH2 intrinsically disordered region in humoral response - Miki Watanabe-Matsui; Shun Kadoya; Kei Segawa; Hiroki Shima; Tadashi Nakagawa; Yuko Nagasawa; Shuichiro Hayashi; Mitsuyo Matsumoto; Mariko Ikeda; Akihiko Muto; Kyoko Ochiai; Long C. Nguyen; et al. (iScience)
Summary: Heme is known to bind to the intrinsically disordered region (IDR) to regulate protein function. The binding of heme to the IDR of transcription factor BACH2 promotes plasma cell differentiation, but the molecular basis is unknown. Heme was found to increase BACH2 IDR interaction with TANK-binding kinase 1 (TBK1). TBK1 inactivated BACH2 by phosphorylation of its IDR, whereas BACH2 repressed TBK1 gene expression. BACH2 phosphorylation by TBK1 inhibited its interaction with the co-repressor NCOR1 and promoted plasma cell differentiation. Heme also induced BACH2 binding to ubiquitin E3 ligase adaptor FBXO22, which polyubiquitinated BACH2 only in the presence of heme in vitro. Mutations of some of the TBK1-mediated phosphorylation sites promoted BACH2-FBXO22 interaction, while additional mutations abrogated their interaction, suggesting that TBK1 can both inhibit and promote BACH2-FBXO22 interaction. Therefore, heme regulates phosphorylation of BACH2 IDR by TBK1 and its interaction with NCOR1 and FBXO22, leading to de-repression of BACH2 target genes in humoral immunity.